Rules, Discretion, and Macro-Prudential Policy - Agur, Itai.; Sharma, Sunil (Washington, D.C. : International Monetary Fund, 2013)
The paper examines the implementation of macro-prudential policy. Given the coordination, flow of information, analysis, and communication required, macro-prudential frameworks will have weaknesses that make it hard to implement policy. And dealing with the political economy is also likely to be challenging. But limiting discretion through the formulation of macro-prudential rules is complicated by the difficulties in detecting and measuring systemic risk. The paper suggests that oversight is best served by having a strong baseline regulatory regime on which a time-varying macro-prudential policy can be added as conditions warrant and permit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet